PENGUATAN EKOSISTEM WISATA DAN INDUSTRI KOPI DESA MELUNG MELALUI PENGELOLAAN DAN PROMOSI BERBASIS DIGITAL - Ranggi Praharaningtyas Aji; Dwi Krisbiantoro; Rida Purnama Sari; Hasirun, Hasirun; Rian Hidayat; Ibnu Romadhon (Nusantara Hasana Journal, 2025)
This community service program (PMM scheme) aimed to empower the BUMDes and Pokdarwis of Melung Village through an integrated digital intervention to address coffee management and tourism marketing issues. Utilizing participatory methods, including Focus Group Discussions (FGD), student-led mentoring (KKN), and the provision of appropriate technology (TTG), the program successfully developed the web application `simelung.org` for asset and financial recording, established standardized coffee processing SOPs, created structured tourism packages, and installed 13 directional signs and 1 mini map. The intervention strengthened institutional governance, improved coffee quality consistency, professionalized destination branding, and built local human resource capacity. In conclusion, synergistic academia-community collaboration supported by a digital approach proved effective in creating a replicable, integrated empowerment model to drive sustainable village economy in line with the SDGs.